An assessment of sand extraction environmental externalities as a source of market failure in Gweru District of Zimbabwe. - Manyumbu, George; Jerie, Steven (ARJHSS Journal, 2022)
This study sought to assess the environmental externalities of sand extraction as a source of market failure in Gweru District. The research instruments used included direct field observations, structured Contingency Valuation Survey (CVS) questionnaire, key informant interviews and secondary data sources. The researcher used purposive sampling to select the key informants for the interview whichincluded two Gweru District Environmental Management Agency officers and the local leaders of Ward 11. Simple random sampling was used to select the respondents for CVS. The interview respondents identified land degradation and increased turbidity in Vhungu and Ngamo Rivers as the major negative environmental externalities of sand extraction in the District. The key informants identified desilting of Vhungu and Ngamo Rivers as the main positive externality. The CVS revealed that only 26.9% of the respondents expressed Willingness To Pay (WTP) for the sand conservation program. Thirty percent of the respondents expressed Willingness to Accept compensation for the loss of open access to the sand resource.The study concludes thatsand extraction is a source of market failures like negative environmental externalities and opportunity costs.The study also recommends that the Government of Zimbabwe must amend the Environmental Management Act (Chapter 20:27) so that sand extraction is also listed in its First Schedule. This would make it a legislative requirement for EIAs to be done prior to any sand extraction project. The government of Zimbabwe must incentivize the use of alternative raw materials so as to reduce the rate of sand extraction.